Marx & Engels Collected Works Vol 23 : Marx and Engels:1871-1874 - Marx, Karl, 1818-1883 (Book collections on Project MUSE., 1980)
Part of a definitive English-language edition, prepared in collaboration with the Institute of Marxism-Leninism in Moscow, which contains all the works of Marx and Engels, whether published in their lifetimes or since. The series includes their complete correspondence and newly discovered works.